Analisis Tindak Tutur Ilokusi dan Nilai-Nilai Pendidikan Karakter dalam Film Jembatan Pensil - Aida Fitria Safra Usman; Chery Julida; Asrol Asrol (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2021)
The moral decadence that has hit Indonesia has given a bad image to the world of education, especially the many films that display the gap in student behavior in each of its scenes. As a result of the spectacle that is less educational, it has an impact on student behavior in school. The purpose of this study is to find a decent spectacle for children who are studied through the actions of ilokusi speech and character values in the film Pencil Bridge. Method article writing with descriptive qualitative approach (literature study). In the collection of data this study uses observation and documentation with techniques to observe and record conversations in films and group them according to the category of speech actions of the ilokusi, in addition to the technique of validity of data in this study in the form of triangulation theory and data analysis using interactive analysis. The results showed that in the film Pencil Bridge contains acts of speech, such as assertive, directive, commissionive, expressive, declarative. In this study, researchers also found a lot of character education value contained in the film Pencil Bridge such as the value of discipline, creative value, value of appreciating achievement and the value of friendship